2016
DOI: 10.1016/j.nicl.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Connectome-scale assessment of structural and functional connectivity in mild traumatic brain injury at the acute stage

Abstract: Mild traumatic brain injury (mTBI) accounts for over one million emergency visits each year in the United States. The large-scale structural and functional network connectivity changes of mTBI are still unknown. This study was designed to determine the connectome-scale brain network connectivity changes in mTBI at both structural and functional levels. 40 mTBI patients at the acute stage and 50 healthy controls were recruited. A novel approach called Dense Individualized and Common Connectivity-based Cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 61 publications
5
23
0
1
Order By: Relevance
“…AFNI motion‐correction algorithms were used to perform more realignment steps with three angular rotations (roll, pitch, and yaw in units of degrees) and three directional displacement (in millimeters) adjustments to further minimize motion artifacts. After these correction steps, no statistical differences were observed in the previous six motion parameters and frame displacement along all temporal frames between MTBI and control groups ( P > 0.05) …”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…AFNI motion‐correction algorithms were used to perform more realignment steps with three angular rotations (roll, pitch, and yaw in units of degrees) and three directional displacement (in millimeters) adjustments to further minimize motion artifacts. After these correction steps, no statistical differences were observed in the previous six motion parameters and frame displacement along all temporal frames between MTBI and control groups ( P > 0.05) …”
Section: Methodsmentioning
confidence: 96%
“…After these correction steps, no statistical differences were observed in the previous six motion parameters and frame displacement along all temporal frames between MTBI and control groups (P > 0.05). 24 Data Analysis SMALL-WORLDNESS ANALYSES. A few key terminologies commonly used in graph theory [27][28][29][30] and this work include: (1) degree (D): equal to the number of connections (edges) attached to each node (ROI).…”
Section: Mri Imagingmentioning
confidence: 99%
“…For example, out of 25 resting-state functional magnetic resonance imaging (rs-fMRI) studies of mTBI, 6 showed only increased FC, [17][18][19][20][21][22] 9 showed only decreased FC, [23][24][25][26][27][28][29][30][31][32] and 10 showed both increased FC in some brain networks/regions and decreased FC in other networks/regions. [33][34][35][36][37][38][39][40][41] Twenty-one of these rs-fMRI studies were concerned with blunt mTBI whereas only four were related to blast mTBI. In the four blast mTBI studies, Gilmore and colleagues found reduced FC between visual network regions and other brain areas, 23 Robinson and colleagues found decreased FC of bilateral primary somatosensory and motor cortices, 28 Han and colleagues found increased within-module FC, but decreased inter-module FC, 33 and Vakhtin and colleagues found decreased FC among various brain networks (default mode network [DMN]-basal ganglia, attention-sensorimotor, frontal-DMN, attentionfrontal, and sensorimotor-sensorimotor).…”
Section: Introductionmentioning
confidence: 99%
“…Otras áreas generales como el cuerpo calloso, siembras grandes en el tallo cerebral, en el tálamo, los lóbulos frontales/temporales y en los tractos largos como el tracto corticoespinal han sido usadas para evaluar estos valores en DWI (35,36,38), siguiendo las recomendaciones para el mapeo general del cerebro con el reciente estudio americano Connectome, que pretende establecer las conexiones cerebrales existentes, y que ha servido de soporte para diferentes estudios en pacientes con trauma craneoencefálico (39)(40)(41).…”
Section: Discussionunclassified